Analytical formulation of hybrid-Trefftz thick plate elements - Petrolito, J. (Computer Assisted Methods in Engineering and Science, 2003)
This paper discusses a domain-based formulation for hybrid-Trefftz thick plate elements. The formulation can be applied to triangular and quadrilateral elements, and enables an analytical formulation of these elements to be used. Techniques for improving the computational efficiency are explored, and a simple and accurate triangular element is formulated in this manner.